2017
DOI: 10.7554/elife.26403
|View full text |Cite
|
Sign up to set email alerts
|

ESCRTs function directly on the lysosome membrane to downregulate ubiquitinated lysosomal membrane proteins

Abstract: The lysosome plays an important role in maintaining cellular nutrient homeostasis. Regulation of nutrient storage can occur by the ubiquitination of certain transporters that are then sorted into the lysosome lumen for degradation. To better understand the underlying mechanism of this process, we performed genetic screens to identify components of the sorting machinery required for vacuole membrane protein degradation. These screens uncovered genes that encode a ubiquitin ligase complex, components of the PtdI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 56 publications
6
114
0
Order By: Relevance
“…Microlipophagy requires ESCRT components, but not the core Atg proteins for the autophagosome formation, when it is induced either by inhibition of phosphatidylcholine biosynthesis or by diauxic shift of the culture (Figure D). Furthermore, microautophagy for the degradation of vacuolar membrane proteins utilizes the ESCRT machinery under different culture conditions . These findings seem reasonable in light of the direct activity of the ESCRT machinery on membrane curvature and formation of luminal vesicles in endosomes, membrane dynamics that are similar to the invagination process of microautophagy.…”
Section: Type 2 Microautophagy With Lysosomal Invaginationmentioning
confidence: 66%
See 1 more Smart Citation
“…Microlipophagy requires ESCRT components, but not the core Atg proteins for the autophagosome formation, when it is induced either by inhibition of phosphatidylcholine biosynthesis or by diauxic shift of the culture (Figure D). Furthermore, microautophagy for the degradation of vacuolar membrane proteins utilizes the ESCRT machinery under different culture conditions . These findings seem reasonable in light of the direct activity of the ESCRT machinery on membrane curvature and formation of luminal vesicles in endosomes, membrane dynamics that are similar to the invagination process of microautophagy.…”
Section: Type 2 Microautophagy With Lysosomal Invaginationmentioning
confidence: 66%
“…The target organelles of these microautophagic pathways include the cytoplasm, ER, portions of the nucleus (piecemeal microautophagy of the nucleus, or PMN), mitochondria, and lipid droplets . In addition, recent studies demonstrated that vacuolar membrane proteins are degraded through this type of microautophagy . Below we summarize three aspects of the molecular machineries discovered in these yeast studies.…”
Section: Type 2 Microautophagy With Lysosomal Invaginationmentioning
confidence: 99%
“…The budding of enveloped viruses from the plasma membrane appears to be an analogous vesiculation process, as the bud neck is again narrow and the ESCRT-III/Vps4 machinery accumulates and is released rapidly (Baumgartel et al 2011, Bleck et al 2014, Feng et al 2013, Jouvenet et al 2011). Other analogous ESCRT-dependent vesiculation processes include ILV budding directly into the vacuole (the yeast equivalent of the lysosome) (Zhu et al 2017, Caspi & Dekker 2018), shedding microvesicle release from the plasma membrane (Choudhuri et al 2014, Matusek et al 2014, Nabhan et al 2012), and possibly also nuclear egress of the Herpes viral core particle (Lee et al 2012) and vesicle secretion at the ciliary transition zone (Diener et al 2015, Wood et al 2013). …”
Section: The Escrt Pathwaymentioning
confidence: 99%
“…We were surprised to observe an unexpected accumulation of strongly LAMP1-positive membranes within the RCV, particularly at late times of infection ( Figure S6). Alternatively, vesicles containing LAMP1 and vATPase may bud from the boundary phagosome membrane into the phagosome lumen similar as described for yeast vacuole transmembrane proteins (McNally, Karim, & Brett, 2017;Zhu, Jorgensen, Li, Chuang, & Emr, 2017) or for microautophagy (Dunn, 1994), depleting the RCV membrane of certain proteins. Alternatively, vesicles containing LAMP1 and vATPase may bud from the boundary phagosome membrane into the phagosome lumen similar as described for yeast vacuole transmembrane proteins (McNally, Karim, & Brett, 2017;Zhu, Jorgensen, Li, Chuang, & Emr, 2017) or for microautophagy (Dunn, 1994), depleting the RCV membrane of certain proteins.…”
Section: Vapa Does Not Rupture Lysosome Membranesmentioning
confidence: 99%